2016
DOI: 10.1097/qad.0000000000000936
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the in-vivo HIV template switching and recombination rate

Abstract: The in-vivo estimated template switching rate is close to the in-vitro estimated rate found in primary T lymphocytes but not macrophages, which is consistent with the majority of HIV infection occurring in T lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…This is not surprising given that all sets of sequences used in the simulation had very low within-alignment diversity (the within T/F mean Hamming distance range per nucleotide per sequence was 0.76–2.93% across all parental pairs), and many of the random recombination breakpoints in our simulation occur in sequence stretches where both parents were identical or nearly identical. As a result, this study alone cannot bound the recombination rate from above, and Cromer et al 31 values are consistent with the lower bounds we obtain.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This is not surprising given that all sets of sequences used in the simulation had very low within-alignment diversity (the within T/F mean Hamming distance range per nucleotide per sequence was 0.76–2.93% across all parental pairs), and many of the random recombination breakpoints in our simulation occur in sequence stretches where both parents were identical or nearly identical. As a result, this study alone cannot bound the recombination rate from above, and Cromer et al 31 values are consistent with the lower bounds we obtain.…”
Section: Resultssupporting
confidence: 89%
“…Template switches occurring in nearly identical regions of the genome are likely to go undetected. Cromer et al 31 modeled this phenomenon and estimated between 5 and 14 template switches per recombinant genome. In this study, we observed a high frequency of recombination breakpoints in our data when both significant and non-significant but potential breakpoints were considered, consistent with what was reported by Cromer et al 31 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although recombination has been intensively studied in cell culture and in vitro, it has been difficult to quantify its contribution to viral genetic diversity in vivo due to the difficulty of detecting and tracking the history of individual viruses. Cromer and colleagues tackled this problem using data obtained from single genome amplification at early time points [ 5 ]. Previous studies have shown that just after infection, viral diversity is sufficiently low to reconstruct the genetic makeup of the founder virus [ 6 ].…”
Section: Main Textmentioning
confidence: 99%